A Consistent Inconsistency—An Interpretationof Sections 23 and 56(1) of the Charter of Human Rights and Freedoms of Québec - Pierre, Barbara (Revue générale de droit)

(untitled) (Éditions Wilson & Lafleur, inc., 1997)
The writer advocates the view that courts interpret statutes so as to achieve their aim; that being justice in the case: as between the parties and in respect of the law. This is identified as the common thread that explains the apparent erratic behaviour of the courts in their use of the various methods or rules of interpretation. The Supreme Court decision, Attorney General of Québec v. 2747-3174 Québec Inc., is analysed against the background of this theory and is seen to give support to it.The court is shown to use various rules of interpretation, which lead the majority to a wide, and the minority to a narrow, interpretation of the Charter of Human Rights and Freedoms of Québec. Yet it is clear that in both cases the rules are merely a means to an end: justice as between the parties and in respect of the law. In context of the case, this means establishing a balance between the competing interests of the State and the citizen that conforms to the law relating to fundamental rights and in particular, the Charter of Human Rights and Freedoms of Québec.As far as the State is concerned, it has a vested interest in confirming the constitutionality of its many administrative tribunals, which play an essential role in enabling the State to discharge its responsibility to govern. Citizens, on the other hand, need to be protected from the violation of their rights, in particular the right to an independent and impartial tribunal in matters relating to the determination of their rights and obligations, or charges brought against them. The Charter must be interpreted so that, in its scope and content, it gives real protection, but, consistent with the separation of powers doctrine, the interpretation must not amount to a usurpation by the courts of the role of the government to govern.The writer concludes that the opposing conclusions of the majority and minority are more a consequence of the difference in the opinion of the judges as to the manner in which the balance should be struck, as opposed to the rules of interpretation used by them.